Immersion in virtual reality experience influences the spatial presence of students at College of Technology and Design - University of Economics Ho Chi Minh City - Nguyễn Thị Thanh Huyền; Trịnh Thuỳ Anh; Dương Thị Thuỳ Trang; Hoàng Việt Linh; Hà Hoàng Minh Trang (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh)
Nowadays, Virtual Reality (VR) has received much attention from researchers. Based on “naive theory”, the research team proposed a conceptual model with two research questions: (1) How does immersion in augmented reality experiences affect spatial presence; (2) How, in the power of imagination, this relationship is changed. The study applied the naive theory and the results of the study showed that immersion in a realistic erectile experience has a positive effect on spatial presence and that ease of visualization plays a mediating role in positive relationship between immersion in virtual reality experiences and spatial presence. Research and conduct surveys with 195 respondents at College of Technology and Design, University of Economics Ho Chi Minh City at the virtual reality experience space. The results of the study help expand the research literature on augmented reality experiences, immersion, and spatial representation in an experimental context.